2017
DOI: 10.1016/j.jclepro.2017.02.190
|View full text |Cite
|
Sign up to set email alerts
|

Solar energy for process heating: A case study of select Indian industries

Abstract: The annual consumption of petroleum products in India was about 221 million metric tons in 2015. Of this, 84% was imported. The Indian industrial sector accounts for about 16%-20% of the total fuel consumption for thermal energy for different heating applications in the temperature range of 50°C-250°C. Solar collectors can meet these temperature requirements and offer the possibility to mitigate the consumption of oil. This study highlights the fact that conversion efficiency from solar energy is much higher f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
20
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(22 citation statements)
references
References 27 publications
0
20
0
2
Order By: Relevance
“…Among the total energy used in industry, 67% is contributed by heat energy. Suresh and Rao [41] reported that with current collector technologies, low-temperature heat demands are most suitable for the integration of solar heat. Solar energy has a significant industrial market in Malaysia given that 30% of the industrial process heat requires temperatures below 100 • C [42].…”
Section: Case Studymentioning
confidence: 99%
“…Among the total energy used in industry, 67% is contributed by heat energy. Suresh and Rao [41] reported that with current collector technologies, low-temperature heat demands are most suitable for the integration of solar heat. Solar energy has a significant industrial market in Malaysia given that 30% of the industrial process heat requires temperatures below 100 • C [42].…”
Section: Case Studymentioning
confidence: 99%
“…So, for example, processes such as various types of drying, cleaning, washing, heating water, pasteurization, and sterilization do not require temperatures above 250 • C, which can easily be achieved using various types of solar collectors. The second most common user of solar collectors is the textile industry, in which many production processes (such as cleaning, drying, washing, pressing) do not require high temperatures [15][16][17]. Depending on the required temperature level of the production process, various types of solar thermal collectors are used, from the most straightforward and cheapest air flat-plate collectors, suitable for temperatures up to 100 • C to the more complex Fresnel collector or parabolic trough collectors for temperatures up to 400 • C [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…The solar thermal collectors are usually broken down into three categories based on the heat transfer fluid (HTF) temperature. Low temperature solar collector (less than 100°C) consists of a flat plate and evacuated tube collectors (ETC), which are able to maintain the hot water and air for residential properties, high temperature collector (over 300°C) [2,3]. Such linear Fresnel collectors and parabolic ducts, are, by and large, designed for the steam generators vapor provision [4].…”
mentioning
confidence: 99%